Autistic autobiography and hermeneutical injustice. (Metaphilosophy, 2021)
This paper examines epistemic injustice in knowledge production concerning autism. Its aim is to further our understanding of the distinctive shapes of the kinds of epistemic injustices against autists. The paper shows how Ian Hacking's work on autistic autobiography brings into view a form of hermeneutical injustice that autists endure with respect to their firsthand accounts of their experiences of autism. It explores how understanding the distinctive shape of this hermeneutical injustice can help us further appreciate dangers and harms of using interpretive frameworks for autistic experience that neglect autists' own contributions to the formation of words and concepts for capturing their experiences. In particular, the paper argues that even when autists are included in knowledge production concerning autistic experience, they remain vulnerable to forms of hermeneutical marginalization that can stifle the coming into being of autistic experience.